2018
DOI: 10.1108/hff-11-2017-0464
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation for fluid droplet impact on discrete particles with coupled SPH-DEM method

Abstract: Purpose A new coupled model is developed to simulate the interaction between fluid droplet collisions on discrete particles (DPs) by using mathematic function. Design/methodology/approach In this model, the smoothed particle hydrodynamics (SPH) is used based on the kernel function and the time step which takes into consideration to the fluid domain in accordance with the discrete element method (DEM) with resistance function. The interaction between fluid and DPs consists of three parts, which are repulsive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Within the framework of the SPH method, the simulation domain is populated by freely moving particles where physical properties are averaged over computational particles using a smoothing kernel function, and the governing equations are discretized on these particles. SPH has been applied to a wide range of applications such as free surface flows (Aly et al , 2013; Leroy et al , 2016; Gotoh et al , 2014), hydrodynamic instabilities (Rahmat et al , 2014; Shadloo and Yildiz, 2011), multi-phase flows (Rahmat et al , 2016; Hopp-Hirschler et al , 2019; Rahmat and Yildiz, 2018; Nasiri et al , 2018), bluff body simulations (Shadloo et al , 2011) and fluid–solid interactions (Rafiee and Thiagarajan, 2009; Tran-Duc et al , 2017; Rahmat et al , 2019; Li et al , 2018).…”
Section: Governing Equationsmentioning
confidence: 99%
“…Within the framework of the SPH method, the simulation domain is populated by freely moving particles where physical properties are averaged over computational particles using a smoothing kernel function, and the governing equations are discretized on these particles. SPH has been applied to a wide range of applications such as free surface flows (Aly et al , 2013; Leroy et al , 2016; Gotoh et al , 2014), hydrodynamic instabilities (Rahmat et al , 2014; Shadloo and Yildiz, 2011), multi-phase flows (Rahmat et al , 2016; Hopp-Hirschler et al , 2019; Rahmat and Yildiz, 2018; Nasiri et al , 2018), bluff body simulations (Shadloo et al , 2011) and fluid–solid interactions (Rafiee and Thiagarajan, 2009; Tran-Duc et al , 2017; Rahmat et al , 2019; Li et al , 2018).…”
Section: Governing Equationsmentioning
confidence: 99%
“…It is demonstrated that the rheological behavior of the surrounding fluid could dramatically affect droplet deformation. Li et al (2018) developed a new coupled model to simulate the interaction between fluid droplet collisions on discrete particles (DPs). Khayyer et al (2023) presented velocity-divergence error mitigating (VEM) and volume conservation shifting (VCS) schemes to enhance the resolution of the continuity equation and satisfy incompressibility conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the per-grid-point operation cost increases drastically. There are other numerical methods such as fictitiousdomain method (DLM), smooth particle hydrodynamics (SPH) (Li et al, 2018), lattice Boltzmann method (LBM) and immersed boundary method (IBM) that avoid grid conformation and provide better fluid-structure coupling capabilities. Combined strategies involving IB-LBM have also been extensively studied for fluid and thermal problems (Adeeb et al, 2018;Bamiro and Liou, 2013).…”
Section: Introductionmentioning
confidence: 99%